Survival Analysis of Training Methodologies and Other Risk Factors for Musculoskeletal Injury in 2-Year-Old Thoroughbred Racehorses in Queensland, Australia - Crawford, Kylie L.; Finnane, Anna; Greer, Ristan M.; Barnes, Tamsin S.; Phillips, Clive J. C.; Woldeyohannes, Solomon M.; Bishop, Emma L.; Perkins, Nigel R.; Ahern, Benjamin J. (Frontiers in Veterinary Science, 2021)
Musculoskeletal injuries (MSI) remain a problem for Thoroughbred racehorses and there is conflicting evidence regarding the effect of age on the incidence of injuries. The ideal time to commence training is strongly debated, with limited evidence. There is also conflicting evidence regarding the effect of high-speed exercise on MSI. The types of MSI vary between two-year-old (2yo) and older horses, with dorsal metacarpal disease (DMD) the most common injury in 2yo horses. This study aimed to determine the risk factors for MSI and whether these were different for DMD than for other types of MSI. We conducted a prospective survey over 56 weeks, from 26 trainers, involving 535 2yo racehorses, 1, 258 preparations and 7, 512 weeks exercise data. A causal approach was used for statistical models. Survival analyses using Cox proportional hazards or Weibull regression models of MSI overall revealed the hazard reduced with increased exposure to high-speed exercise (HR 0.98, 95% CI 0.97, 0.99, p<0.001), increased number of training preparations (HR 0.58, 95% CI 0.50, 0.67 p<0.001), increased rest before training preparation (HR 0.89, 95% CI 0.83, 0.96, p=0.003) and increased dam parity (HR 0.86, 95% CI 0.77, 0.97, p=0.01). The hazard of injury increased with increasing age that training commenced (HR 1.13, 95% CI 1.06, 1.19, p<0.001). Factors protective against DMD and MSI included: increased total cumulative distance (HR 0.98, 95% CI 0.96, 0.99, p=0.003) and total cumulative days gallop (HR 0.96, 95% CI 0.92, 0.99, p=0.03), number of the training preparations (HR 0.43, 95% CI 0.30, 0.61, p<0.001). The age that training commenced was harmful for both DMD (HR 1.17, 95% CI 1.07, 1.28, p<0.001 and MSI. The use of non-ridden training modalities was protective for DMD (HR 0.89, 95% CI 0.81, 0.97, p=0.008), but not MSI overall. Male sex increased the hazard of DMD compared to females (HR 2.58, 95% CI 1.20, 5.56, p=0.02), but not MSI. Early identification of horses at increased risk of MSI and close monitoring of these horses could reduce the impact of MSI. An understanding of how training methodologies affect the hazard of MSI also mitigates the risk of injury.